Design Of Intrusion Control Panel - Mr.S.Arunprathap,Mr.S.Naveenkumar,Mr.K.Sethu,Mr.S.Vigneshwaran (International Journal of Modern Agriculture, 2021)
This reference design details IEC ESD, EFT, Surge Protected and AC- coupling of RS-485 signals. Although this signal is always typically DC coupled which are using AC-coupling has several advantages. AC-coupling allows many transceivers to operate with the wide/large common-mode offsets, enabling wide/long-distance communication without routing an additional ground wire. This protection is useful in industry based application that requires data transfers across wide distances with a minimum number of wires. Industrial based network services such as RS-485are expected to withstand/sustain harsh system oriented transient levels in their final end applications without getting damaged. This event process will be caused due to electrostatic discharging process during handling and inductive load interruption and/or relay bounce contact or strikes of lighting.TIDA-00731 shows the practical example which is used to protect the most sensitive components which are against their lethal transients. This project moves through the following such as TIA/EIA-485 standards and the IEC 61000-4-x transient test standards and the implementation of system-level protection level which are against the transients and overall schematic layout designs.